Polychaete annelid (segmented worms) abundance and species composition in the proximity (6–9 km) of the Deep Water Horizon (DWH) Oil Spill in the Deep Gulf of Mexico. (July 2016) - Qu, Fangyuan; Nunnally, Clifton C.; Lemanski, Joseph R.; Wade, Terry L.; Amon, Rainer M.W.; Rowe, Gilbert T.
Abstract: Polychaete annelids (segmented worms) dominated the macrobenthos in sediments located 6–9 km from the Deep Water Horizon (DWH) Oil Spill site five months after the event, based on nine 0.2 m 2 box core samples. Numbers of species, abundance, and biodiversity indices in the polychaete taxa were significantly lower than pre-spill values from similar depths in the eastern Gulf of Mexico (GoM). Both non-selective and selective deposit feeders were the most frequent feeding guilds, as expected, but their abundances were significantly lower. An increase in the number of carnivorous Sigalionidae may be a response to an accumulation of petroleum hydrocarbons on the sediment. The concentration of oil in the sediments was low and the source of the oil remains equivocal. Multivariate analyses illustrated the differences between communities near the DWH and those from prior studies in similar deep GoM habitats. In summary, Deep Water Horizon Oil Spill appears to have had a measurable impact on the polychaetes.